Securing wireless sensor networks: an identity-based cryptography approach. (28th October 2010) - Szczechowiak, Piotr; Scott, Michael; Collier, Martin
Key distribution is a challenging problem in Wireless Sensor Networks (WSNs). The system has to be simple, energy efficient and at the same time offer a high level of security. This paper shows that all these requirements can be addressed by using an Identity-Based Cryptography (IBC) approach. We explain why IBC is a better security solution than methods based on standard public key and symmetric key mechanisms. We also suggest a practical identity-based key agreement scheme that does not require any communication between two parties. This scheme simplifies the key management in the network by reducing the number of required keys, making the system scalable. Evaluation results prove that the software implementation is practical on a broad range of sensor platforms and different CPU architectures. Comparison with the state of the art shows that identity-based key distribution is a superior security solution for WSNs with better resistance against known attacks.